Synergistic Effect of the Lactoperoxidase System and Cinnamon Essential Oil on Total Flora and Salmonella Growth Inhibition in Raw Milk - Chiraz Abbes; Ahlem Mansouri; Ahmed Landoulsi (Journal of Food Quality)
Despite its antibacterial and antipathogenic effects, the heat treatment of milk induces undesirable changes that can be noted in the overall properties of ultrahigh temperature (UHT) milk, such as changes in nutritional and organoleptic properties. Our goal is to find new nonthermal antibacterial technologies for the preservation of raw milk (RM). This study investigates the possible synergistic effect of using a combination of the lactoperoxidase system (LS) and 3 μg mL−1 of cinnamon essential oil (cinnamon EO) to inactivate the total flora of milk and Salmonella Hadar (S. Hadar). The LS was activated with 30 mg L−1 sodium percarbonate and 14 mg L−1 of sodium thiocyanate. Using this approach, we obtained a synergistic effect with a complete inhibition of the activity of the total flora of the milk and S. Hadar after 12 hours at 25°C. In addition, the attainment of synergy was defined when the inhibitory effect of the two compounds together was greater than the effect observed by each compound added alone. Moreover, the monitoring of the synergistic effect at 4°C for 5 days showed complete inhibition of total flora for 3 days and for S. Hadar it was up to 5 days. To summarize, the current study clearly identified a new inhibitory combination that may be used in food-based applications.